The Influence of Cognitive Impairment on Postoperative Outcomes. Issue 1 (10th January 2023) - Blair, Emilie M.; Levine, Deborah A.; Hu, Hsou Mei; Langa, Kenneth M.; Kabeto, Mohammed U.; Waljee, Jennifer
Abstract : Objective: To examine differences in rates of elective surgery, postoperative mortality, and readmission by pre-existing cognitive status among Medicare beneficiaries undergoing surgery. Background: MCI is common among older adults, but the impact of MCI on surgical outcomes is understudied. Methods: We conducted a retrospective cohort study of individuals ≥65 who underwent surgery between 2001 and 2015 using data from the nationally-representative Health and Retirement Study linked with Medicare claims. Cognitive status was assessed by the modified telephone interview for cognitive status score and categorized as normal cognition (score: 12–27), MCI (7–11), and dementia (<7). Outcomes were 30- and 90-day postoperative mortality and readmissions. We used Cox proportional hazard models to estimate the risk of each outcome by cognition, adjusting for patient characteristics. Results: In 6, 590 patients, 69.9% had normal cognition, 20.1% had MCI, and 9.9% had dementia. Patients with MCI (79.9%) and dementia (73.6%) were less likely to undergo elective surgery than patients with normal cognition (85.9%). Patients with MCI had similar postoperative mortality and readmissions rates as patients with normal cognition. However, patients with dementia had significantly higher postoperative 90-day mortality (5.2% vs 8.4%, P = 0.002) and readmission rates (13.9% vs 17.3%, P = 0.038). Conclusion: Patients with self-reported MCI are less likely to undergo elective surgery but have similar postoperative outcomes compared with patients with normal cognition. Despite the variability of defining MCI, our findings suggest that MCI may not confer additional risk for older individuals undergoing surgery, and should not be a barrier for surgical care.